Digital Literation in Increasing Reading Interest and Overcoming Hoax News from Social Media in Basic School Students - Awaliyah, Anisa Nurul; Hartati, Tatat; Tursiva, Erva (International Conference on Elementary Education, 2021)
Digital literacy is one of the reading movements that elementary school students must have in the 21st century. Social media allows students to be actively involved in increasing the reading interest of elementary school students to obtain new information. The role of digital use in today's modern era is very effective and efficient to increase reading interest, but in the context of language learning, teachers still have to be guided by using social media facilities so that students don't fall into consuming hoax or fake news. From the hoax news that is spread, researchers suspect that increasing reading interest from social media through digital literacy has a very big effect. This study aims to determine and analyze the relationship between digital literacy and reading interest from social media in dealing with hoax stories of elementary school students. The method used in this research is literature study or literature study. The results showed that in general, the application of digital literacy was able to increase reading interest in overcoming hoax news from social media. Furthermore, suggestions from researchers so that students have good reading interests need to be trained continuously by applying digital literacy in elementary schools.